Extended Irreversible Thermodynamics - Jou, David; Lebon, Georgy; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This is the 4th edition of the highly acclaimed monograph on Extended Irreversible Thermodynamics, a theory that goes beyond the classical theory of irreversible processes. In contrast to the classical approach, the basic variables describing the system are complemented by non-equilibrium quantities. The claims made for extended thermodynamics are confirmed by the kinetic theory of gases and statistical mechanics. The book covers a wide spectrum of applications, and also contains a thorough discussion of the foundations and the scope of the current theories on non-equilibrium thermodynamics. For this new edition, the authors critically revised existing material while taking into account the most recent developments in fast moving fields such as heat transport in micro- and nanosystems or fast solidification fronts in materials sciences. Several fundamental chapters have been revisited emphasizing physics and applications over mathematical derivations. Also, fundamental questions on the definition of non-equilibrium temperature, entropy, fluctuations of fluxes and boundary conditions are revisited and presented in a modern way. Detailed solutions for more than 130 problem sets presented in this book, as well as a wide bibliography on extended irreversible thermodynamics are accessible at the http://telemaco.uab.es site.
General Theory -- Classical, Rational and Hamiltonian Formulations of Non-equilibrium Thermodynamics -- Extended Irreversible Thermodynamics: Evolution Equations -- Extended Irreversible Thermodynamics: Non-equilibrium Equations of State -- Microscopic Foundations -- The Kinetic Theory of Gases -- Fluctuation Theory -- Information Theory -- Linear Response Theory -- Computer Simulations -- Selected Applications -- Hyperbolic Heat Transport in Rigid Conductors -- Heat Transport in Micro- and Nano-systems -- Waves in Fluids: Sound, Ultrasound, and Shock Waves -- Generalised Hydrodynamics -- Non-classical Diffusion, Thermo-diffusion and Suspensions -- Electrical Systems and Micro-devices Modelization -- From Thermoelastic Solids to Rheological Materials -- Thermodynamics of Polymer Solutions Under Shear Flow -- Relativistic Formulation -- Viscous Cosmological Models and Cosmological Horizons.
Keywords: Physics; Thermodynamics; Amorphous substances; Complex fluids; Statistical physics; Dynamical systems; Heat engineering; Heat transfer; Mass transfer; Nanotechnology; Physics; Thermodynamics; Engineering Thermodynamics, Heat and Mass Transfer; Soft and Granular Matter, Complex Fluids and Microfluidics; Statistical Physics, Dynamical Systems and Complexity; Nanotechnology; Electronic books